Analisis Kewenangan Atributif Camat dalam Penyelenggaraan Pemerintahan di Kecamatan Bontonompo Kabupaten Gowa - Riski Wahyuni (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2018)
This research aims to determine the implementation attribute authority of the Subdistrict Head in the community empowerment activities in the Subdistrict Bontonompo of the Regency Gowa and the factors that influence. To achieve that goal, used method of research qualitative with parse the data is descriptive. The technique collection of the data by observation, interview, as well as document and archives by using technical analysis descriptive qualitative.The result of the research showed: First, impelementation attribute authorityof the Subdistrict Head in the implementation of government in the Subdistrict Bontonompo of the Regency Gowa can be said good enough and is based on the national legislation. But in the implementation there are indicators are not maximal yet, as like encourage public pastisipation in the Musrembang forum. Second, the factor that influence implementation attribute authority of the Subdistric Head in the Subdistrict Bontonompo of the Regency Gowa include the factor inhibiting and supporters. The factors inhibiting are limitedness budget and the lack of capabilities of human resources. The factors that be supporting are leadership of Subdistrict Head and Government policy